Avaliação in vitro do potencial prebiótico do subproduto do do processamento do pedúnculo do caju(Anacardium occidentale L.) frente à Lactobacillus spp. - Menezes, Francisca Nayara Dantas Duarte (2016)
The cashew (Anacardium occidentale L.) is a tropical, popular and well accepted fruit, due its nutritional characteristics and sensory attributes. The processing of the cashew pseudo-fruit (also called peduncle) generates the main byproduct which represent up to 20% of the total weight of the pseudo-fruit. In the last years, studies verifying the prebiotic potential of the byproducts from the processing of the cashew peduncle are scarce or nonexistent. In this context, the present study aimed to evaluate in vitro the prebiotic effects of a lyophilized powder obtained from the byproduct of the cashew peduncle (named CAP) against different probiotic strains of Lactobacillus, such as: L. acidophillus LA-05, L. casei L-26 and L. paracasei L-10. The growth and viable cell numbers of the Lactobacillus strains were monitored in Mann, Rogosa and Sharpe (MRS) broth containing CAP (20 g/L), glucose (20 g/L) and fructooligosaccharides – FOS (20 g/L), during 48 h. Some parameters related to the metabolic activity of the probiotic strains, cultivated in these different culture media, were evaluated, such as pH, production of organic acids and consumption of sugars. Similar viable cell count for each tested Lactobacillus strain in the different culture media were observed, count reached 8.5 - 9.0 log CFU/mL and pH values at approximately 4.0 after 48 h of cultivation. The growth of these Lactobacillus strains in MRS broth containing glucose, FOS or CAP resulted in a decrease of pH, production of organic acids (acetic, citric, malic, formic and lactic) and consumption of sugars (glucose, fructose and maltose) during the incubation time, indicating an intense bacterial metabolic activity. Overall, the tested Lactobacillus strains showed similar capability to ferment the FOS and the CAP, although some differences related to the production of organic acids and consumption of sugars were detected. The results showed that the CAP possesses a prebiotic potential effect toward Lactobacillus strains. These findings may stimulate the agro-industrial sector to valorize the byproducts from the cashew pseudo-fruit processing as an added-value ingredient to the food industry.